Bibliometric analysis of beneficial cannabis research: Performance analysis and science mapping from 2012 to 2022 and focus on Morocco - Fatima-Zahrae Laaboudi; Mohamed Rejdali; Amin Salhi; Abedellah Elyoussfi; Abdelmonaem Talhaoui; Hassan Amhamdi; M’hamed Ahari (Toxicology Reports, 2024)
Beneficial cannabis use has sparked growing interest among researchers, leading to an increase in empirical studies exploring its phytochemistry and applications. However, understanding the overall research orientation remains limited. This study aims to bridge this gap by conducting a bibliometric analysis of 7841 documents published from 2012 to 2022. The analysis reveals an annual growth rate of 16.83 %, with a focus on medicine, pharmacology, toxicology, pharmaceutics, biochemistry, genetics, molecular biology, and neuroscience. Performance analysis highlights metrics of sources, countries, affiliations, and authors, while science mapping identifies keywords, thematic evolution, and citation/co-authorship patterns. Notably, Morocco, despite its limited initial contributions, has shown recent steady growth in cannabis research, with an annual growth rate of 14.31 % and a 51.72 % international collaborative rate. This study provides valuable insights into established fields and potential research directions in cannabis research, paving the way for a deeper understanding among the audience. With the changing legal status of cannabis, research is rapidly expanding, focusing on the plant's bioactive compounds, pharmacological properties, and therapeutic applications. The dominant subject areas are medicine, pharmacology, toxicology, pharmaceutics, biochemistry, genetics, molecular biology, and neuroscience, covering nearly 76 % of the studied papers. Despite limited initial contributions from African countries like Morocco due to legal restrictions, beneficial cannabis research is gaining interest. Future research should prioritize in-depth exploration of specific compounds, comparative studies of cannabis-based products, and rigorous clinical trials. Fostering international collaborations and bridging the gap between research and policymakers are crucial for harnessing the full potential of cannabis while mitigating potential risks. This study serves as a reference for researchers to identify current orientations, blind areas, and gaps in cannabis research, offering suggestions for future studies.